Extracting characteristics of adaptive tool for rehabilitation: a qualitative insight from the expert user’s practice - Mat Yusof, Nurhikma; Raja Ahmad Effendi, Raja Ahmad Azmeer; Bolong, Jusang; Romli, Muhammad Hibatullah (Science and Engineering Research Support Society, 2019)
Adaptive tool (AT) is a generic term describing the prescription aid given to the patient during assessment or practice to performing activities of daily living (ADL) for recovery process in rehabilitation. It is configured according to the patient’s body condition and is set to specifications of either low, medium or high technology. The goal of this study is to identify AT's characteristics from the point of view of expert users engaged in rehabilitation adaptation-innovation development. In this study, the expert users recruited were six professionals consisting of occupational therapists and designers with experience in rehabilitation and medical tool design that was subjected to a semi-structured interview regarding their respected expertise. Both expertise was selected due to their involvement with rehabilitation tool, in order to conclude both experience in a holistic conclusion vein for adaptation design understanding. The interview sessions were audio-recorded, transcribed, summarized and latter analyzed via thematic analysis. The themes developed were: i) fundamental characteristics, ii) technical characteristics, and iii) management characteristics. This study exposes the needs and challenges associated with patient recovery process fulfillment. Future studies should afford more focus on developing strategies to enhance mutual understandings in adaptation-innovation between design and rehabilitation for more effective recovery of patients.